2004
DOI: 10.1074/jbc.m405225200
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Myxococcus xanthus CarA Repressor Is an Autonomously Folding Domain That Mediates Physical and Functional Interactions with Both Operator DNA and Antirepressor Protein

Abstract: Expression of the Myxococcus xanthus carB operon, which encodes the majority of the enzymes involved in light-induced carotenogenesis, is down-regulated in the dark by the CarA repressor binding to its bipartite operator. CarS, produced on illumination, relieves repression of carB by physically interacting with CarA to dismantle CarA-DNA complexes. Here, we demonstrate that the N-and C-terminal portions of CarA are organized as distinct structural and functional domains. Specifically, we show that the 78 N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…S1C). A plasmid construct with the gene for C1 or C2 (or CarH, as a control) expressed from a constitutive promoter (12,20) was introduced into the M. xanthus strain lacking endogenous CarA and CarH, where it integrates at an unlinked site in the chromosome. Unlike the Car C recipient strain, the resulting transformants were Car (+) : yellow in the dark only in the presence of B 12 and red in the light, just like the control strain with CarH (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C). A plasmid construct with the gene for C1 or C2 (or CarH, as a control) expressed from a constitutive promoter (12,20) was introduced into the M. xanthus strain lacking endogenous CarA and CarH, where it integrates at an unlinked site in the chromosome. Unlike the Car C recipient strain, the resulting transformants were Car (+) : yellow in the dark only in the presence of B 12 and red in the light, just like the control strain with CarH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1B). Besides their autonomously stable, N-terminal DNA-binding domains (CarANt and CarHNt, respectively) that recognize the same operator (12,19,20), CarA and CarH have C-terminal domains (CarACt and CatHCt, respectively) with a B 12 -binding motif of the type found in enzymes like methionine synthase (6,12,(21)(22)(23). However, only CarH requires B 12 for its repressor activity (12).…”
mentioning
confidence: 99%
“…Oligomerization could also play an important role in driving the binding of CarA to the low affinity site pII. Indeed, deletion of its oligomerization domain leads to a constitutive light-independent expression of P B in vivo (55). The particular spatial arrangement and the differential repressor binding affinities of pI and pII in the design of the CarA operator may have evolved to achieve the proper finetuning in the control of carB expression, as discussed next.…”
Section: Discussionmentioning
confidence: 97%
“…CarA represses the transcription of carotenoid biosynthesis genes in the dark, and light-induced sequesterization of CarA induces expression of the biosynthesis genes, 4,5) but there is no evidence regarding the direct response of CarA to an illumination signal. The relation between LitR function and illumination was also unclear in S. coelicolor A3(2), since our attempts to obtain true knockout mutants for litR and litQ in this organism failed.…”
mentioning
confidence: 99%
“…In M. xanthus, light-induced carotenogenesis is clearly observed in media supplied with vitamin B12. 14) Recently, PerezMarin et al 5) suggested that CarA binds vitamin B12 in vitro. The property of absorbing blue light, which is a characteristic of vitamin B12 proteins such as methionine synthase, 15) implies that the cofactor plays a significant role in the light-dependent function of the family of transcriptional regulators.…”
mentioning
confidence: 99%